Feminist Perspectives on the Dominance of Lawsuit Divorce in the Religious Court of Jepara - Inna Fauziatal Ngazizah; Wahyu Kholid Hidayatullah (QURU’: Journal of Family Law and Culture, 2026)
Divorce is a growing social phenomenon in Indonesia, particularly within the jurisdiction of Religious Courts. This study examines the dominance of lawsuit divorce (cerai gugat) cases in the Religious Court of Jepara during 2021–2022 from a feminist perspective. Although divorce is legally permissible in Islamic law, it remains socially undesirable due to its implications for family integrity and social stability. This research employs a socio-legal approach, combining normative legal analysis with empirical data derived from interviews, observation, and documentation. The findings indicate that lawsuit divorce significantly outnumbers talaq divorce due to economic hardship, domestic violence, abandonment, and irresponsible spousal behavior. From a feminist standpoint, the increasing number of lawsuit divorce cases reflects both women’s agency in seeking justice and the persistence of structural gender inequality within marriage. This study contributes to the discourse on Islamic family law and gender justice by highlighting the intersection between legal frameworks and women's lived experiences.